RELEVANSI NILAI-NILAI PENDIDIKAN ISLAM DALAM KEPEMIMPINAN KHALIFAH ABU BAKAR ASH-SHIDDIQ - Armi Riski Gultom; Ardian Al Hidaya; Rosyida Nurul Anwar; Marzuki (Yayasan Baitul Hikmah al-Zain, 2025)
Abu Bakar can be a role model for various parties and fields of science, because in his leadership Caliph Abu Bakar Ash-Siddiq did not only think about one side, such as defense and the economy, but he also focused on the field of education. So from the various political policies implemented by Caliph Abu Bakar, educational values ​​can be drawn that can be implemented in the current conditions of Islamic education. The research method used in this research is qualitative research. The type of research used is qualitative descriptive research which aims to determine the values ​​of Islamic education in the leadership of Caliph Abu Bakar Ash-Siddiq. During the period of Abu Bakar Ash-Siddiq's caliphate as leader of the Muslims, there were various values ​​relevant to Islamic education to be discussed, namely: 1) The importance of ensuring that every aspect of Islamic education not only teaches monotheism as a theological belief but also builds awareness. spiritual and moral strength in students. 2) Good examples and building understanding that example is the core of effective leadership and has a positive impact. 3) Today's Islamic education needs to teach students to collaborate, discuss and respect various views in the decision-making process.